Evaluating Entrepreneurship Education - Weber, Richard; SpringerLink (Online service) (Wiesbaden : Gabler Verlag, 2012)
Entrepreneurship education at tertiary institutions ranks high on policy agendas in Europe and the US. The increase in resources allocated to this kind of education comes along with a growing demand for justifying these investments. A better understanding of the size and nature of entrepreneurship education effects is critical. Richard Weber analyzes the effects of a large-scale compulsory entrepreneurship course on students' entrepreneurial intentions. Moreover, he highlights the role of social interactions among students in building entrepreneurial skills. The results yield important implications for public policy, sponsors, and lecturers of entrepreneurship education.
Keywords: Economics; Entrepreneurship; Economics/Management Science; Entrepreneurship